The occupation of looking for work: An interpretative phenomenological analysis of an individual job-seeking experience. Issue 3 (3rd July 2017) - de Bruyn, Marna; Cameron, Josh
ABSTRACT: This qualitative study explored the meaning of job-seeking, as a human experience and occupation, as it is understood by an individual job-seeker within the United Kingdom. Interpretative phenomenological analysis was used to understand the meaning of job-seeking as a lived experience. A series of three, in-depth interviews were conducted with a single participant at various stages of the job-seeking experience. After individual and cross analyses of interview transcripts, three master themes were developed that demonstrated how the job-seeking experience was understood. These were: (1) understanding the self and identity, (2) understanding relationships, (3) understanding job-seeking as a journey. These results are discussed in the context of previous studies of job-seeking and occupational perspectives that focus on meaning in human occupation. The authors conclude that job-seeking is a rich human occupation in which the form, function and meaning are influenced by internal and external factors related to the person, their occupations and environment. Future research could build on these insights by considering the efficacy of these internal and external supports and how job-seeking varies across different cultural and social contexts.